Molecular and Cellular Functions of the Linker Histone H1.2 - Lai, Shuting; Jia, Jin; Cao, Xiaoyu; Zhou, Ping-Kun; Gao, Shanshan (Frontiers in Cell and Developmental Biology, 2022)
Linker histone H1.2, which belongs to the linker histone family H1, plays a crucial role in the maintenance of the stable higher-order structures of chromatin and nucleosomes. As a critical part of chromatin structure, H1.2 has an important function in regulating chromatin dynamics and participates in multiple other cellular processes as well. Recent work has also shown that linker histone H1.2 regulates the transcription levels of certain target genes and affects different processes as well, such as cancer cell growth and migration, DNA duplication and DNA repair. The present work briefly summarizes the current knowledge of linker histone H1.2 modifications. Further, we also discuss the roles of linker histone H1.2 in the maintenance of genome stability, apoptosis, cell cycle regulation, and its association with disease.